y=X^3-m(X^2)-(2(m^2)-7m+7)X+2(m-1)(2m-3)

y=X^3-m(X^2)-(2(m^2)-7m+7)X+2(m-1)(2m-3)

bởi Vo Ngoc ngày 13/09/2017

tìm m de hàm đồng biến trên (2; +vc)

Câu trả lời (1)

  • TXĐ: D=R
     
    YCBT \Leftrightarrow Y' >= 0 \forall x>= 2 \Leftrightarrow  
    \Leftrightarrow  
    G'(x)=6x-2m =0 \Leftrightarrow x= m/3
    TH1: [TEX]m/3 = 2 \Leftrightarrow m =6 \Rightarrow Loai (thay vao y' la biet)[/TEX]
    TH2:m >= 6 \Rightarrow  
    TH3:m <= 6 \Rightarrow  
    KL:

    bởi Vo Ngoc ngày 13/09/2017
    Like (0)
Gửi câu trả lời Hủy

 

Các câu hỏi có liên quan